Cyclic deformation behavior of a high-strength low-alloy (HSLA) magnesium alloy with heterostructures - H. Wang; D.T. Zhang; C. Qiu; D.L. Chen (Journal of Magnesium and Alloys)
Strain-controlled cyclic deformation behavior of a high-strength low-alloy (HSLA) Mg-1.2Zn-0.1Ca alloy fabricated via low-temperature extrusion at 150 °C was investigated at different strain amplitudes. Due to the partial dynamic recrystallization (DRX) during extrusion, the extruded HSLA magnesium alloy consisted of a unique heterostructure containing coarse unDRX grains and ultra-fine DRX grains of 0.8 µm, leading to a high tensile yield strength of 374 MPa and an elongation of 14%. The HSLA magnesium alloy exhibited cyclic stabilization at strain amplitudes of ≤0.4%, while cyclic hardening occurred at strain amplitudes of ≥0.6%. In contrast, the homogenized alloy with a uniform coarse-grained microstructure showed a strong cyclic hardening characteristic. Compared with the homogenized alloy, the HSLA magnesium alloy had a significantly higher cyclic stress level at all strain amplitudes, along with a longer fatigue life at lower and intermediate strain amplitudes owing to its higher monotonic strength. However, the homogenized alloy showed a longer fatigue life at a high strain amplitude of 0.8 % due to its better ductility and stronger capacity of storing deformation. While {10–12}<10−11> extension twinning occurred in both the homogenized and HSLA samples at high strain amplitudes, twins were primarily formed in the coarse unDRX grains in the compressive phase during cyclic deformation due to the c-axes of unDRX grains perpendicular to the loading direction, with twinning in the ultra-fine DRX grains being suppressed. The low-cycle fatigue life of both the homogenized and HSLA samples can be well predicted through an accumulative damage model based on the strain-energy density calculation and intrinsic fatigue toughness concept.